2010
DOI: 10.1159/000321716
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Rifampin-Moxifloxacin-Metronidazole Combination Therapy in Hidradenitis Suppurativa

Abstract: Background: Antibiotics have been shown to improve hidradenitis suppurativa (HS) patients but complete remission is rare using these treatments. Objective: To assess the efficacy and safety of a combination of oral rifampin, moxifloxacin and metronidazole in long-lasting refractory HS. Methods: We retrospectively studied 28 consecutive HS patients including 6, 10 and 12 Hurley stage 1, 2 and 3 patients, respectively. Complete remission, defined as a clearance of all inflammatory lesions including hypertrophic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
87
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(92 citation statements)
references
References 46 publications
3
87
0
2
Order By: Relevance
“…For severe or therapy-resistant patients, the combination of rifampicin, moxifloxacin, and metronidazole is an alternative therapeutic option [54]. Metronidazole was originally intended as an antiprotozoal agent that later proved very effective for Gram-negative anaerobic bacteria.…”
Section: Rifampicin Moxifloxacin and Metronidazole Triple Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…For severe or therapy-resistant patients, the combination of rifampicin, moxifloxacin, and metronidazole is an alternative therapeutic option [54]. Metronidazole was originally intended as an antiprotozoal agent that later proved very effective for Gram-negative anaerobic bacteria.…”
Section: Rifampicin Moxifloxacin and Metronidazole Triple Therapymentioning
confidence: 99%
“…Moxifloxacin is not metabolized by cytochrome P450, therefore its availability is not affected when taken together with rifampicin. In a retrospective study by Lamber et al [54], 28 HS patients were treated with a combination of rifampicin (10 mg/kg once daily), moxifloxacin (400 mg daily), and metronidazole (500 mg three times daily). Sixteen patients in this study showed complete remission and another 12 patients showed a partial response [54].…”
Section: Rifampicin Moxifloxacin and Metronidazole Triple Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…), either alone or preceded by systemic ceftriaxone (1 g daily) was effective in 16 of 28 patients with Hurley stage II and III disease. 90 Main adverse events of the treatments were gastrointestinal disorders (64% of patients) and vaginal candidiasis (35% of females). Reversible tendinopathy and hepatitis occurred in 4 and 1 patient, respectively.…”
Section: 31-systemic Antibioticsmentioning
confidence: 99%
“…Other rifampin combinations have not had the same successes; recent study evaluation rifampin-moxifloxacin-flagyl required 12 months of therapy to reach effect in 57% of patients [14]. Additionally groups have tested dapsone showing 62% non-efficacy, with an 8% cessation in treatment for side effects [15]. A notable finding of the review is the duration of therapy required before effect is attained.…”
Section: Antibioticsmentioning
confidence: 99%